2017
DOI: 10.1186/s12879-017-2819-5
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, discussion and non-prescribed use of HIV pre-exposure prophylaxis among persons living with HIV/AIDS in Italy: a Nationwide, cross-sectional study among patients on antiretrovirals and their treating HIV physicians

Abstract: BackgroundBefore Pre-Exposure Prophylaxis (PrEP) was officially recommended and made available, a few surveys among gay and bisexual men, and persons living with HIV/AIDS (PLWHA), identified an informal use of antiretrovirals (ARVs) for PrEP among HIV-negative individuals. Before PrEP availability in Italy, we aimed to assess whether PLWHA in Italy shared their ARVs with HIV-negative individuals, whether they knew people who were on PrEP, and describe the level of awareness and discussion on this preventive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Women in this study had a higher level of knowledge compared to other studies based on at risk women in the US in which PrEP knowledge ranged from almost 0 to 33% [ 23 , 61 , 63 ]. This result may be a consequence of the population sampled here, who may be more connected to HIV prevention services and organizations [ 64 ]. Regarding PrEP interest, women in this study expressed relatively low (18.0%) interest, which is comparable to another US study citing only 20% willingness to use PrEP among Caribbean immigrant women, but contrasts with other reports of high (60–65%) interest among at risk women in the US and internationally [ 23 , 60 , 61 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Women in this study had a higher level of knowledge compared to other studies based on at risk women in the US in which PrEP knowledge ranged from almost 0 to 33% [ 23 , 61 , 63 ]. This result may be a consequence of the population sampled here, who may be more connected to HIV prevention services and organizations [ 64 ]. Regarding PrEP interest, women in this study expressed relatively low (18.0%) interest, which is comparable to another US study citing only 20% willingness to use PrEP among Caribbean immigrant women, but contrasts with other reports of high (60–65%) interest among at risk women in the US and internationally [ 23 , 60 , 61 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with previous studies among sexually active MSM before oral FTC/TDF was licensed for HIV prevention in other settings. 21,[68][69][70] We also observed that some informal PrEP users did not seek medical advice before initiation nor were they adherent to the dosing or quarterly testing schedule. Suboptimal use of PrEP in a medically unsupervised way poses both health risks to the users as well as implementation challenges and ethical issues to HIV prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…In the second section, sexual behavior and habits were evaluated (items 7–22). These items were adapted from a published study [ 15 ] and from an online survey conducted in Spain in 2017 [ 12 ]. We added two items regarding the relational life of the subject (items 9–10), as the presence of different kinds of relation has been previously associated with risky behaviors [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another study was conducted in Italy in order to evaluate knowledge, attitudes and practices regarding PrEP and antiretroviral therapy in a sample of persons living with HIV/acquired immune deficiency syndrome (AIDS) patients. In this study, 45.6% of the patients stated that they were informed about PrEP; however, this result comes from a highly selected sample, informed about HIV and in contact with an infectious disease specialist [ 15 ]. Hence, this sample is not representative of the population which can obtain the highest benefit from PrEP use, namely HIV-negative subjects at high risk of contagion, such as MSM.…”
Section: Introductionmentioning
confidence: 99%